Combined Visible Plasmons of Ag Nanoparticles and Infrared Plasmons of Graphene Nanoribbons for High‐Performance Surface‐Enhanced Raman and Infrared Spectroscopies. Issue 1 (7th December 2020) - Nong, Jinpeng; Tang, Linlong; Lan, Guilian; Luo, Peng; Li, Zhancheng; Huang, Deping; Shen, Jun; Wei, Wei
Abstract: Ag nanoparticles (NPs) modified graphene nanoribbons (GNRs) are proposed to function as the high‐performance shared substrates for surface‐enhanced Raman and infrared absorption spectroscopy (SERS and SEIRAS). This is realized by modulating the localized plasmonic resonances of Ag NPs in visible region and GNRs in mid‐infrared region simultaneously, so as to selectively employ each resonance to acquire SERS and SEIRAS on a single substrate. As a proof of concept, shared substrates are prepared by fabricating GNRs on a Fabry–Pérot like cavity, followed by depositing a thin Ag film with annealing treatment to achieve Ag NPs. Complementary Raman and infrared active vibrational modes of rhodamine 6G molecules can be extracted from the SERS and SEIRAS spectra. By optimizing the dimension of Ag NPs, SERS enhancement factors at the order of 10 5 can be achieved, which are comparable with or even larger than that of the reported shared substrates. Meanwhile, various polyethylene oxide vibrational modes can be recognized with maximum SEIRAS amplification up to 170 times, which is one order larger than that of the reported graphene plasmonic infrared sensors. Such plasmonic nanosensor with excellent SERS and SEIRAS performance exhibits promising potential for biosensing applications on an integrated lab‐on‐a‐chip strategy. Abstract : A shared substrate is proposed to realize the high performance surface‐enhanced Raman and infrared absorption spectroscopy (SERS and SEIRAS) simultaneously employing Ag nanoparticles modified graphene nanoribbons. Complementary Raman and infrared active vibrational modes of rhodamine 6G molecules can be extracted from SERS and SEIRAS spectra. SERS enhancement factors at the order of 10 5 and maximum SEIRAS amplification up to 170 times (one order larger improvement) can be achieved.